Possible layered lithospheric anisotropy around Longmenshan Faults by teleseismic S wave splitting and receiver functions - Wang, An-Jian; Gao, Yuan (Frontiers in Earth Science, 2024)
This study conducts an in-depth analysis of seismic anisotropy around the Longmenshan Faults, utilizing a dataset of about 7710 earthquake catalogs from July 2007 to March 2023. We applied S wave splitting and receiver function methods to examine Pms and XKS waveforms collected from 12 fixed broadband stations across Gansu and Sichuan provinces. Our analysis revealed significant variations in seismic anisotropy between the crust and lithosphere, marked by distinct fast wave directions and delay times. These characteristics point to the possibility for layered anisotropy within the region. A two-layer anisotropy inversion analysis at key stations further delineated the differential anisotropic behaviors between the crust and the upper mantle, underscoring the impact of local geological structures and mantle dynamics. Crucially, our study posits the existence of layered anisotropy around the Longmenshan Fault Zone, a finding that significantly advances our comprehension of the region's seismic anisotropy and adds a vital dimension to our understanding of its subsurface structural intricacies and tectonic evolution.